Testing calpain inhibition in tumor endothelial cells: novel targetable biomarkers against glioblastoma malignancy - Guarnaccia, Laura; Navone, Stefania Elena; Begani, Laura; Barilla, Emanuela; Garzia, Emanuele; Campanella, Rolando; Miozzo, Monica; Fontana, Laura; Alotta, Giovanni; Cordiglieri, Chiara; Gaudino, Chiara; Schisano, Luigi; et al. (Frontiers in Oncology, 2024)
Introduction. Glioblastoma IDH-wildtype (GBM) is the most malignant brain tumor in adults, with a poor prognosis of about 15 months after diagnosis. Most patients suffer from a recurrence in less than one year, and this renders GBM a life-threatening challenge. Among molecular mechanisms driving GBM aggressiveness, angiogenesis mediated by GBM endothelial cells (GECs) deserves consideration as a therapeutic turning point. In this scenario, calpains, a family of ubiquitously expressed calciumdependent cysteine proteases, emerged as promising targets to be investigated as a novel therapeutic strategy and prognostic tissue biomarkers. Methods. To explore this hypothesis, GECs were isolated from n=10 GBM biopsies and characterized phenotypically by immunofluorescence (IF). The expression levels of calpains were evaluated by qRT-PCR and Western Blot, and their association with patients' prognosis was estimated by Pearson correlation and Kaplan Mayer survival analysis. Calpain targeting efficacy was assessed by a time-and dose-dependent proliferation curve, MTT assay for viability, Caspase-3/7 activity, migration and angiogenesis in vitro, gene and protein expression level modification. Results. Immunofluorescence confirmed the endothelial phenotype of our primary GECs. A significant overexpression was observed for calpain-1/2/3 (CAPN) and calpain-small-subunits-1/2 (CAPNS1), whereas calpastatin gene, the calpain natural inhibitor, was reported downregulated. A significant negative correlation was observed between CAPN1/CAPNS1 and patient overall survival. GEC challenging revealed that the inhibition of calpain-1 exerts the strongest proapoptotic efficacy, so GEC mortality reached the 80%, confirmed by the increased activity of Caspase-3/7. Functional assays revealed a strong affection of in vitro migration and angiogenesis. Gene and protein expression proved a downregulation of MAPK, VEGF/VEGFRs and Bcl-2, as well as an upregulation of Caspases and Bax-family mediators. Conclusion. Overall, the differential expression of calpains and the correlation with patient survival suggest a novel promising target pathway, whose blockade showed encouraging results toward precision medicine strategies.